Effect of explicit and implicit components of psychologists’ mental experience on their parental competence - Gusakova, Marina (Journal of Education, Health and Sport, 2021)
The purpose of this research was to determine the effect of various components of psychologists’ mental experience (ME) on their parental competence (PC) when dealing with children of primary school age. We have distinguished three factors – professional attitude, professional competence and professional learning, dividing each into a number of components relating to explicit and implicit experience. For instance, explicit representation of professional attitude in terms of communication with children is a psychologist’s self-assessment scale, and implicit representation is a degree of openness of cognitive position as willingness to solve problems. Explicit representation of psychologist’s professional competence is his/her work experience in his/her major (school psychologist), and implicit representation is reflexivity of cognitive style built by competent professionals. Professional learning for psychologists takes two forms: explicit learning, which is a conscious acquisition of knowledge and skills through trainings and seminars, and implicit learning, which is undirected, for example, through research and writing articles. It has turned out that explicit and implicit components of mental experience have a different effect on such parameters of psychologists’ parental competence as feedback efficiency, level of feedback detail and predictability of feedback usefulness. In other words, we have established that professional mental experience of psychologists may shape up their parental competence, making it both high and low. It is important to know that implicit (and often unconscious) components of mental experience have as much effect as its explicit components. We believe that study of implicit components of professional learning may contribute to improvement of psychologists’ professional training and development of a professional’s mature personality.